Pemanfaatan Aplikasi Wattpad sebagai Media Publikasi Digital dalam Meningkatkan Keterampilan Menulis Teks Cerita Fiktif (Fictional Story) - Yuhafliza Yuhafliza; Nia Astuti; Agusliana Agusliana; Rahmi Hayati (Aliterasi (Jurnal Pendidikan, Bahasa, dan sastra), 2023)
This learning innovation aims to utilize the Wattpad application as a medium used for digital publication of literary works to improve the skills of writing fictional story texts for students at MTsN 2 Aceh Utara. This innovation is used and developed with the aim that MTsN students who have talents and interests in the field of writing can recognize and master several writing applications as a medium for digital publication of their literary works in the form of fictional story texts. One of the steps that must be taken by teachers and students is to download the Wattpad application which will be used as a learning medium in the field of writing skills. The use of the Wattpad digital application as a Digital Publication Media is practiced in class IX A of MTsN 2 Aceh Utara, which consists of 25 students. From the process of using the Wattpad Application as a Digital Publication Media, data was obtained that by using the digital application students already had their own accounts and started publishing their work. It can be concluded that the use of the Wattpad Application as a Digital Publication Media of literary works in the form of fictional story texts can improve students' writing skills.